A crunched seed preparation system - Shamsuddin, Rosnah; Yunus, Robiah (2010)
The present invention generally relates to a machinery system for preparing a crunched seed from a seedy fruit for example Jatropha Curcas L. (Jatropha) fruit. The present invention provides a complete process of preparing the crunched seeds; from crunching to separating the end products accordingly. The crunching mechanism involves multiple crunching mechanisms.